2019
DOI: 10.1002/pon.5185
|View full text |Cite
|
Sign up to set email alerts
|

Stability and change of postchemotherapy symptoms in relation to optimism and subjective stress: A prospective study of breast cancer survivors

Abstract: Objectives: Inconsistent findings were reported about the course of postchemotherapy symptoms; specifically, the effect of changes in optimism and perception of subjective stress on the evolution of symptoms remains understudied. This prospective study aimed (a) to examine the course of postchemotherapy symptoms of emotional distress, fatigue, and cognitive difficulties among breast cancer survivors and (2) to assess the effect of changes in optimism and subjective stress on the trajectory of these symptoms. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Mean scores were calculated, with higher scores indicating more intense symptoms. Previous studies using the Hebrew version reported high internal reliability ( α = 0.91 to 0.92 26 ). The internal reliability (Cronbach's α ) without this item was α = 0.85.…”
Section: Methodsmentioning
confidence: 89%
“…Mean scores were calculated, with higher scores indicating more intense symptoms. Previous studies using the Hebrew version reported high internal reliability ( α = 0.91 to 0.92 26 ). The internal reliability (Cronbach's α ) without this item was α = 0.85.…”
Section: Methodsmentioning
confidence: 89%
“…Other studies showed that although levels of psychological distress decrease about a year postdiagnosis, for about a third of survivors, levels of distress remain chronically elevated for years and increase the risk of clinically significant depression (Carlson et al, 2014). In contrast, in a few studies, low mean scores of psychological distress were reported for breast cancer survivors at 1-2 years post-treatment (Cohen, Levkovich, Pollack, & Fried, 2019;Maass et al, 2015).…”
Section: -3mentioning
confidence: 98%